2009
DOI: 10.4049/jimmunol.0901334
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TGF-β1 and IL-15 Induce FOXP3+ γδ Regulatory T Cells in the Presence of Antigen Stimulation

Abstract: Several subsets of αβ regulatory T cells (Tregs) have been described and studied intensively, but the potential regulatory role of γδ T cells remains largely unclear. Lymphocytes expressing γδ TCR are involved in both innate and adaptive immune responses, and their major adult human peripheral blood subset (Vγ9Vδ2) displays a broad reactivity against microbial agents and tumors. In this study we report that γδ T lymphocytes with regulatory functions (Vδ2 Tregs) are induced in vitro in the presence of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 35 publications
13
126
1
1
Order By: Relevance
“…Depending on the culture conditions, Vc9/Vd2 T cells clearly assume different functions including distinct cytokine profiles [49,74,72,[124][125][126], and hence more research is needed to delineate whether Vc9/Vd2 T-APCs may induce different 'flavors' of CD4 + T cell responses (Th1, Th2, Th17, Th22, Treg), and what the signals involved in such a polarization are. In this respect, our preliminary findings suggest that under appropriate conditions Vc9/Vd2 T-APCs are able to induce considerable IL-22 expression in naive CD4 + T cells [C.J.T., M.E.…”
Section: Priming Of Cd4 + and Cd8 + T Cells By Vc9/vd2 T Cells: A Newmentioning
confidence: 99%
“…Depending on the culture conditions, Vc9/Vd2 T cells clearly assume different functions including distinct cytokine profiles [49,74,72,[124][125][126], and hence more research is needed to delineate whether Vc9/Vd2 T-APCs may induce different 'flavors' of CD4 + T cell responses (Th1, Th2, Th17, Th22, Treg), and what the signals involved in such a polarization are. In this respect, our preliminary findings suggest that under appropriate conditions Vc9/Vd2 T-APCs are able to induce considerable IL-22 expression in naive CD4 + T cells [C.J.T., M.E.…”
Section: Priming Of Cd4 + and Cd8 + T Cells By Vc9/vd2 T Cells: A Newmentioning
confidence: 99%
“…In these trials, IL-2 also elevated the frequency of Tregs, which can inhibit cd T-cell responses or even induce regulatory cd T cells, according to in vitro experiments. 47,48 The reverse situation, however, might also occur in these patients, as phosphoantigen-activated cd T cells can overcome Tregs 49 and TGF-b immunosuppressive functions. 50 The above trials demonstrated that Tregs were not significantly induced by these regimens involving only low doses of IL-2, and they did not offer evidence of Treg-based cd T-cell immunosuppression.…”
Section: Safety Of CD T-cell Activation In Patientsmentioning
confidence: 99%
“…Importantly, however, they can be skewed towards distinct effector functions depending on the microenvironment, in analogy to, and even beyond, the emerging plasticity of CD4 1 ab cells. As such, under appropriate culture conditions, Vg9/Vd2 T cells divert from the 'default' Th1/CTL-like phenotype and assume features reminiscent of Th2 cells [27,29], Th17 cells [30,31], Treg cells [32] and even professional APCs [33]. Our earlier microarray studies revealed that Vg9/Vd2 T cells express a range of T FH -associated molecules when stimulated with HMB-PP in the presence of IL-21 suggesting a potential role in the GC reaction [27].…”
Section: Introductionmentioning
confidence: 99%